1930
DOI: 10.1002/zaac.19301920111
|View full text |Cite
|
Sign up to set email alerts
|

Dichtemessungen bei hohen Temperaturen. X. Über die direkte Auftriebsmethode und die Dichte schmelzflüssiger Metalle, insbesondere von Eisenlegierungen bei Temperaturen bis 1600°

Abstract: Eine neue Meßvorrichtung zur Feststellung des spezifischen Volumens von schmelzflüssigen Metallen bei höchsten Temperaturen nach dem Prinzip der direkten Auftriebsmethode, bei der die Einwirkung von Gasen mit Sicherheit ausgeschlossen werden kann, wird angegeben.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1933
1933
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The current negative temperature coefficient (1.59~1.83 9 10 À3 ) was higher than that of Fe-C reported by Jimbo and Cramb (5.36~8.28 9 10 À4 ). However, considering the large scatter in the previous data (4.6 9 10 À4~1 .6 9 10 À3 ) of the Fe-C alloy, [4][5][6][7][8] the current results are acceptable. Consequently, based on these results, the density of Fe-Mn-C alloys can be described by Eqs.…”
mentioning
confidence: 33%
“…The current negative temperature coefficient (1.59~1.83 9 10 À3 ) was higher than that of Fe-C reported by Jimbo and Cramb (5.36~8.28 9 10 À4 ). However, considering the large scatter in the previous data (4.6 9 10 À4~1 .6 9 10 À3 ) of the Fe-C alloy, [4][5][6][7][8] the current results are acceptable. Consequently, based on these results, the density of Fe-Mn-C alloys can be described by Eqs.…”
mentioning
confidence: 33%
“…3), the early results of Pascal [13], are shown to be completely at variance with the more recent results of other workers. Since the work of Widawski and Sauerwald [44] using the same method as Pascal has yielded results more in accord with contemporary values, e.g. Lucas [34] and Kirshenbaum [60], it must be concluded that Pascal's work is unreliable.…”
Section: 1 Results For Pure Metalsmentioning
confidence: 54%